Cardiovascular deconditioning and impact of artificial gravity during 60-day head-down bed rest—Insights from 4D flow cardiac MRI - Rabineau, Jeremy; Issertine, Margot; Hoffmann, Fabian; Gerlach, Darius; Caiani, Enrico G.; Haut, Benoit; van de Borne, Philippe; Tank, Jens; Migeotte, Pierre-François (Frontiers in Physiology, 2022)
Microgravity has deleterious effects on the cardiovascular system. We evaluated some parameters of blood flow and vascular stiffness during 60 days of simulated microgravity in head-down tilt (HDT) bed rest. We also tested the hypothesis that daily exposure to 30 minutes of artificial gravity (1 g) would mitigate these adaptations. 24 healthy subjects (8 women) were evenly distributed in three groups: continuous artificial gravity, intermittent artificial gravity, or control. 4D flow cardiac MRI was acquired in horizontal position before (-9 days), during (5, 21, and 56 days), and after (+4 days) the HDT period. The false discovery rate was set at 0.05. The results are presented as median [first quartile; third quartile]. No group or group × time differences were observed so the groups were combined. At the end of the HDT phase, we reported a decrease in the stroke volume allocated to the lower body (-30% [-35%; -22%]) and the upper body (-20% [-30%; +11%]), but in different proportions, reflected by an increased share of blood flow towards the upper body. The aortic pulse wave velocity increased (+16% [+9%; +25%]), and so did other markers of arterial stiffness (CAVI, CAVI_0). In males, the time-averaged wall shear stress decreased (-13% [-17%; -5%]) and the relative residence time increased (+14% [+5%; +21%]), while these changes were not observed among females. Most of these parameters tended to or returned to baseline after 4 days of recovery. The effects of the artificial gravity countermeasure were not visible. We recommend increasing the load factor, the time of exposure, or combining it with physical exercise. The changes in blood flow confirmed the different adaptations occurring in the upper and lower body, with a larger share of blood volume dedicated to the upper body during (simulated) microgravity. The aorta appeared stiffer during the HDT phase, however all the changes remained subclinical and probably the sole consequence of reversible functional changes caused by reduced blood flow. Interestingly, some wall shear stress markers were more stable in females than in males. No permanent cardiovascular adaptations following 60 days of HDT bed rest were observed.